2011
DOI: 10.1111/j.1542-474x.2011.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reproducibility of Heart Rate Recovery after Treadmill Exercise Test

Abstract: Maximal heart rates and the decline of heart rate to the 5th minute on recovery phase after treadmill exercise test have short-term reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…These results have short term reproducibility,6 and both HRR1 and HRR2 have been validated, with one or the other or both having been used in 83% of the epidemiological studies included in the survey noted above. Both Lipinski et al 7 and Gorelik et al 8 compared HRR1, HRR2, HRR3 and HRR5, and found HRR2 to be the better predictor of all-cause mortality.…”
Section: Discussionmentioning
confidence: 87%
“…These results have short term reproducibility,6 and both HRR1 and HRR2 have been validated, with one or the other or both having been used in 83% of the epidemiological studies included in the survey noted above. Both Lipinski et al 7 and Gorelik et al 8 compared HRR1, HRR2, HRR3 and HRR5, and found HRR2 to be the better predictor of all-cause mortality.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies with small sample size reported HRR values in athletes (Buchheit & Gindre, ; Borresen & Lambert, ; Lamberts et al ., ; Barak et al ., ), but the results are not comparable because of different protocols used for assessment of HRR. Although it has been shown to be a reproducible variable, the method used for obtaining HRR produces great variations in its values and could influence reproducibility (Buchheit et al ., ; Barak et al ., ; Tulumen et al ., ; Adabag & Pierpont, ; Boullosa et al ., ). In this study, we used maximal exercise protocol, having the subjects sit after 1 min of active recovery, and calculated HRR as the absolute value of the decrease from HR peak to rates 1, 2 and 3 min postexercise.…”
Section: Discussionmentioning
confidence: 99%
“…As there were no significant differences between test and retest mean values for all indices of HRR, except HR120s, it is possible to state that, in general, there is no systematic error between test and retest. Similarly, previous studies with healthy subjects also reported absence of systematic bias in raw HR (Bosquet et al ., ; Tulumen et al ., ; Boullosa et al ., ) and relative HRR (Bosquet et al ., ; Al Haddad et al ., ; Arduini et al ., ; Tulumen et al ., ; Dupuy et al ., ; Boullosa et al ., ) indices.…”
Section: Discussionmentioning
confidence: 99%
“…When agreement was indicated by CVs (percentage of their respective means), higher CVs were obtained for relative HRR indices (8·6–45·6%) than for raw HR indices (4·6–7·2%). A similar pattern has been previously reported in healthy subjects (Bosquet et al ., ; Tulumen et al ., ; Boullosa et al ., ) and may reflect a limitation of the calculus with the raw HR indices likely to be similar in terms of absolute HR values for the calculation of CV (i.e. numerator and denominator values were similar to each other and hence, smaller CV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation